Escherichia albertii in Wild and Domestic Birds - Oaks, J. Lindsay (Centers for Disease Control and Prevention, 2010)
Escherichia albertii has been associated with diarrhea in humans but not with disease or infection in animals. However, in December 2004, E. albertii was found, by biochemical and genetic methods, to be the probable cause of death for redpoll finches (Carduelis flammea) in Alaska. Subsequent investigation found this organism in dead and subclinically infected birds of other species from North America and Australia. Isolates from dead finches in Scotland, previously identified as Escherichia coli O86:K61, also were shown to be E. albertii. Similar to the isolates from humans, E. albertii isolates from birds possessed intimin (eae) and cytolethal distending toxin (cdtB) genes but lacked Shiga toxin (stx) genes. Genetic analysis of eae and cdtB sequences, multilocus sequence typing, and pulsed-field gel electrophoresis patterns showed that the E. albertii strains from birds are heterogeneous but similar to isolates that cause disease in humans.